Northeast Pacific warm blobs sustained via extratropical atmospheric teleconnections - Jian Shi; Hao Huang; Alexey V. Fedorov; Neil J. Holbrook; Yu Zhang; Ruiqiang Ding; Yongyue Luo; Shengpeng Wang; Jiajie Chen; Xi Hu; Qinyu Liu; Fei Huang; et al. (Nature Communications, 2024)
Abstract Large-scale marine heatwaves in the Northeast Pacific (NEP), identified here and previously as ‘warm blobs’, have devastating impacts on regional ecosystems. An anomalous atmospheric ridge over the NEP is known to be crucial for maintaining these warm blobs, also causing abnormally cold temperatures over North America during the cold season. Previous studies linked this ridge to teleconnections from tropical sea surface temperature anomalies. However, it was unclear whether teleconnections from the extratropics could also contribute to the ridge. Here we show that planetary wave trains, triggered by increased rainfall and latent heat release over the Mediterranean Sea accompanied by decreased rainfall over the North Atlantic, can transport wave energy to the NEP, guided by the westerly jet, and induce a quasi-barotropic ridge there. Our findings provide insights into extratropical teleconnections sustaining the NEP ridge, offering a source of potential predictability for the warm blobs and temperature fluctuations over North America.